Universal Behavior Screening and Early Warning System Indicators in Middle Schools - Graybill, Emily; Lewis, Scott; Anghel, Ella; Awan, Sofia; Barger, Brian; Salmon, Ashley (Psychology in the schools, 2025)
ABSTRACT Early warning indicator and intervention systems (EWS) have been promoted to identify students at risk of school underperformance or dropout. Current EWS systems typically include administrative data on attendance, behavior incidents requiring disciplinary action, and course performance. This study tested whether specific emotional and behavioral risk symptoms measured by a student self‐report universal screener administered in the fall can predict the three EWS indicators after controlling for fall behavioral incidents and whether they account for some of the variance in EWS attributed to demographic characteristics. Using data from 3307 middle school students, we found that after accounting for fall disciplinary issues, conduct problems predicted poorer student outcomes, but hyperactivity/inattention was predictive of better course performance. Peer problems predicted lower performance in some courses, while emotional problems predicted better performance as well as fewer behavioral issues. We also found that these symptoms accounted for some of the variance in EWS attributed to race and gender. The results suggest that student self‐report universal screening can complement existing EWS measures and potentially identify at‐risk students who may not otherwise be identified through traditional EWS indicators. Summary School district early warning system indicators often do not include a measure of emotional and behavior risk or a student self‐report measure of early risk. Among middle schoolers, students with internalizing concerns such as peer and emotional problems may not be at risk on other early warning system indicators – such as attendance, behavior, and course performance ‐ and would likely be missed as needing early intervention without behavior screening data. Student self‐report universal behavior screening measuring internalizing and externalizing concerns can complement existing early warning systems to identify at‐risk students early, particularly those with internalizing concerns who may not be at risk on other early warning system indicators.